2018
DOI: 10.1038/s41398-018-0240-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota regulates mouse behaviors through glucocorticoid receptor pathway genes in the hippocampus

Abstract: Gut microbiota has an important role in the immune system, metabolism, and digestion, and has a significant effect on the nervous system. Recent studies have revealed that abnormal gut microbiota induces abnormal behaviors, which may be associated with the hypothalamic–pituitary–adrenal (HPA) axis. Therefore, we investigated the behavioral changes in germ-free (GF) mice by behavioral tests, quantified the basal serum cortisol levels, and examined glucocorticoid receptor pathway genes in hippocampus using micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
133
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(157 citation statements)
references
References 58 publications
3
133
1
4
Order By: Relevance
“…For instance, a seminal study reported that GF male mice have an overreactive HPA axis leading to increased concentrations of corticosterone and adrenocorticotropic hormone (ACTH) following a stressful stimulus (Sudo et al, ). These findings have been replicated several times (Clarke et al, ; Luo et al, ; K. A. Neufeld, Kang, Bienenstock, & Foster, ; K. M. Neufeld, Kang, Bienenstock, & Foster, ); and have been expanded to GF male rats (Crumeyrolle‐Arias et al, ). Furthermore, an in‐depth epigenetic study reported that gene expression in the brain of GF male mice was significantly different from controls, the most notable differences were observed in the hippocampus, cortex, striatum, and cerebellum (Heijtz et al, ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, a seminal study reported that GF male mice have an overreactive HPA axis leading to increased concentrations of corticosterone and adrenocorticotropic hormone (ACTH) following a stressful stimulus (Sudo et al, ). These findings have been replicated several times (Clarke et al, ; Luo et al, ; K. A. Neufeld, Kang, Bienenstock, & Foster, ; K. M. Neufeld, Kang, Bienenstock, & Foster, ); and have been expanded to GF male rats (Crumeyrolle‐Arias et al, ). Furthermore, an in‐depth epigenetic study reported that gene expression in the brain of GF male mice was significantly different from controls, the most notable differences were observed in the hippocampus, cortex, striatum, and cerebellum (Heijtz et al, ).…”
Section: Introductionmentioning
confidence: 78%
“…The most notable differences are seen in the brain and the immune system, both particularly relevant in addressing anxiety and depression‐like behaviors. Moreover, both depression and anxiety disorders are heavily influenced by stress pathways such as the hypothalamus–pituitary–adrenal (HPA) axis, which can be strongly modified by the gut microbiome composition (Luo et al, ; Sudo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In several paralleled researches, MDD patients showed speci c features of gut microbes differing from normal controls [5][6][7][8]. Several studies have reported that transplantation of stool from MDD patients into rodents could lead to depression-like behaviors, which had be used to establish animal models of MDD [5,9,10]. The similar phenomenon was observed in fecal bacteria transplantation between animal models.…”
Section: Introductionmentioning
confidence: 83%
“…Its function therefore may be linked to that of DENND3. AMPD3 (adenosine monophosphate deaminase 3) is also involved in energy metabolism and may also play a role in microbial interactions with the host (206).…”
Section: Slc16a3mentioning
confidence: 99%